Bioactive and biodegradable hydrogel based on the dermal matrix loaded with microspheres containing vascular endothelial growth factor (VEGF) and interleukin (IL)-10 accelerated the healing of diabetic wounds in rats - Zihan Wang; Jia Liu; Runpei Deng; Yang Yang; Chen Fangfang; Shi Yonghui (Regenerative Therapy)
Diabetic wounds are among the most common and costly complications in diabetic patients. As a result, numerous studies have been conducted to explore effective approaches for accelerating the wound healing process. Biological hydrogels are frequently used for wound healing due to their favorable properties compared to other materials. In this study, we evaluated the effect of a bioactive and degradable hydrogel based on dermal matrix (HDM) encapsulated with microspheres containing vascular endothelial growth factor (VEGF) and interleukin (IL)-10 on promoting wound healing in diabetic rats. Forty-five diabetic rats were randomly assigned to three groups (n = 15): control, HDM, and HDM encapsulated with microspheres containing VEGF and IL-10 (HDMM). In addition, non-diabetic untreated rats (healthy group) were considered as control (n = 15). Wound assessments were performed on days 7, 14, and 21. The results demonstrated significant improvements in wound closure rate, fibroblast and blood vessel counts, collagen density, concentration levels of TGF-β and VEGF cytokines, and biomechanical parameters in the treatment groups compared to the control group, with the most pronounced effects observed in the HDMM group. Additionally, the HDMM group exhibited a greater reduction in neutrophil and macrophage counts, as well as decreased levels of TNF-α and IL-1β cytokines compared to the other groups. In conclusion, the HDM loaded with microspheres containing VEGF and IL-10 showed a more significant effect in promoting the healing of diabetic wounds.